Salt Lake Community College Veterans Services: A Model of Serving Veterans in Higher Education. Issue 172 (December 2015) - Ahern, Aaron; Foster, Michael; Head, Darlene
Abstract : This chapter outlines the birth and growth of a veterans' program in Salt Lake City, Utah, and discusses next steps in spurring additional innovations and advancements to improve service for student veterans in community colleges.